ChemInform Abstract: A Cu/Pd Cooperative Catalysis for Enantioselective Allylboration of Alkenes. Issue 17 (April 2016) - Jia, Tao; Cao, Peng; Wang, Bing; Lou, Yazhou; Yin, Xuemei; Wang, Min; Liao, Jian
Abstract: The catalytic asymmetric three‐component reaction of various styrenes, Bpin‐Bpin, and allyl carbonates is presented.